Roles of autophagy in HIV infection. Issue 1 (11th November 2014) - Dinkins, Christina; Pilli, Manohar; Kehrl, John H
Abstract : Autophagy is a major cellular pathway, which at basal levels regulates and maintains the cytoplasmic environment through the capture, isolation and digestion of intracellular materials in a specialized structure called an autophagosome. The unique ability of autophagy to degrade large targets, such as damaged and surplus organelles, intracellular microbes and protein aggregates, has made it a prime focus in inflammation and microbial research. Indeed, autophagy has been shown to be involved in a number of infectious and inflammatory pathologies, by which it may confer protection against intracellular microbes, be targeted by microbes for evasion or be hijacked for microbe biogenesis. In addition, autophagy helps regulate the intracellular and global immune response to both extracellular and intracellular pathogens. Here we review the current literature on the interactions between autophagy and HIV among different immune cells and discuss new research that re‐emphasizes the role of inflammation in HIV‐mediated CD4 + T cell death. Abstract : The January 2015 issue contains a Special Feature on Autophagy and Immunity. Autophagy is an essential process to maintain cellular homeostasis and functions. It is responsible for the lysosome‐mediated degradation of damaged proteins and organelles, and dysregulation of this pathway contributes to the development of a variety of diseases in man, including: diabetes, neurodegeneration and cancer. Recent studies have illuminated the importance of the regulatory pathways that control autophagy and the wide range of physiological processes it regulates in humans. Immunology and Cell Biology thanks the coordinators of this Special Feature ‐ Jim Harris and Justine Mintern ‐ for their planning and input. Further background information on this important topic is available through the accompanying web focus which links to related articles from across Nature Publishing Group.